Effect of foliar applications of boron on the phenological development and fruit set of purple passion fruits (Passiflora edulis f. edulis Sims) (2018)
Gulupa or purple passion fruit is a native fruit produced in Colombia and exported to different international markets. Some problems affecting crop production are related to flowering and fruiting, mainly because of nutrient limitations, such as boron (B) deficiency. The objective of this research was to evaluate the effect of foliar boron spraying on the phenological development and fruit set of gulupa plants grown under field conditions. This study was carried out in an experimental plantation in the municipality of Pasca (Cundinamarca, Colombia), located at 2,006 m a.s.l. The treatments consisted of three doses of boric acid: T50, T100, T150, and a control, T0, with foliar spray applications in the floral bud and fruit set stages, during two consecutive productive cycles. The length of the productive branches, number of internodes, percentage of fruit set, fruit diameter, and emission of flower buds and fruits were evaluated. The foliar applications of B at the evaluated rates increased the length of the secondary branches, emission of flower buds and fruits, and percentage of fruit set. The best growth results in the first and second cycles were achieved with the T50 treatment although, in terms of fruit set percentage, the T100 treatment was optimal for the first production cycle (85.19%), followed by the T50 treatment for the second production cycle (90%). The fruits of the treatment 0.3 kg ha-1 developed a larger equatorial diameter from 21 days after planting (dap), reaching the maximum diameter (55.68 mm) at 136 dap.